Praxis and the ends of action in Suarez - Ginocchio, David (Anuario Filosófico, 2017)
I will try to show how Suarez's model of praxis allows for the coordination of intellect and will to generate actions through the integration of ends. A special sense of causality is studied that adds a practical overlay to actions: while actions remain an external mode of the effect, they can be contingent insofar as they are produced by a free agent with particular ends in mind. I will argue that the appearance of these ends is only possible through a habitual understanding of praxis, which is a subjective consideration of reality as 'operable'.
Keywords: Francisco Suárez; praxis; human action; ends; WOS; Scopus